2013
DOI: 10.1155/2013/960954
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adherence to Antiretroviral Treatment in Harari National Regional State, Eastern Ethiopia

Abstract: Background. The efficacy of antiretroviral treatment (ART) depends on strict adherence to the regimen, but many factors have been identified for nonadherence. Method. To identify the factors for non-adherence to ART, a cross-sectional study was conducted on people living with human immunodeficiency virus (HIV) and attending the ART service at Hiwot Fana and Jugal hospitals; it was done from October to December, 2010. Adherence was defined as taking 95% of the prescribed doses in the week before the survey. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 15 publications
12
46
2
1
Order By: Relevance
“…Based on this, the prevalence of ART adherence level in selected health facilities were (65%). This result is comparable with study done in Yirgalem hospital with the prevalence of ART adherence level (74%) [18], similar study in Felegehiwot hospital in Gonder town show that level of adherence among HIV infected patients were (82.7%) [19]. This result show that the prevalence of art adherences level is smaller when compared with study done in Gonder and ART patients in Dire Dawa may use different substance abuse like chat which is one of the factors that contribute for forgets and ignorance to take medicine on time.…”
Section: Discussionsupporting
confidence: 88%
“…Based on this, the prevalence of ART adherence level in selected health facilities were (65%). This result is comparable with study done in Yirgalem hospital with the prevalence of ART adherence level (74%) [18], similar study in Felegehiwot hospital in Gonder town show that level of adherence among HIV infected patients were (82.7%) [19]. This result show that the prevalence of art adherences level is smaller when compared with study done in Gonder and ART patients in Dire Dawa may use different substance abuse like chat which is one of the factors that contribute for forgets and ignorance to take medicine on time.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings were also made in Moi Teaching and Referral Hospital in which it was found out that most of the patients who failed to adhere to ART treatment were in the age bracket of 36-45 years and were either divorced, widowed or separated [17]. Contrary findings were made in Ethiopia where it was founnd that married patients had least adherence to ART treatment [20]. …”
Section: Influence Of Demographic Factors On Art Adherencesupporting
confidence: 64%
“…Similar findings were made in Ethiopia where it was reported that presence of support from family did not translate to better ART adherence as patients might miss support at working places and other places outside home [20]. Contrary findings were made in Malawi where it was also revealed that there was better adherence among patients who get some form of support in their homes, hospital, or among their friends, as compared with non-supported patients [22].…”
Section: Influence Of Social Factors On Art Adherencementioning
confidence: 61%
“…Over half of the population reported being in a relationship, however no correlation was found between adherence and being in a relationship vs. not being in a relationship. Findings in this sample are similar to other studies in which marital status was not related to adherence; the researchers concluded that the role of gender and household dynamics may prevent females from successfully adhering to ART and the fact that partners may not be aware of their HIV-positive status (Mitiku, Abdosh, & Teklemariam, 2013;Peltzer et al, 2010;Skovdal et al, 2011). concluded that closer doctor-patient relationships and promoting self-efficacy among patients were predictors of successful of ART adherence, more so than education level Arrivillaga et al, 2011).…”
Section: Hypothesis 3bsupporting
confidence: 84%
“…Researchers found that women reported selective adherence to ART in order to protect themselves and their children (Smith & Waitzman, 1994;Bourne, 2009;Waldron et al, 1996;Mitiku, Abdosh, & Tekelmariam, 2014) and noted that taking medication reminded them of their diseases (Mitiku et al, 2014;Peltzer et al, 2010). Researchers have found that social forces, such as racism, sexism and poverty, not only aggravate perceived stigma when all are present, but especially more where political violence and social inequalities also exist (Sumari-deBoer et al, 2012).…”
Section: Perceived Stigma and Adherence In Femalesmentioning
confidence: 99%